Analisis Dampak Harmonisa terhadap Efisiensi Energi pada Pengoperasian Inverter Air Conditioner - Nofan Rullyanto Tinambunan; Rahmaniar (Jurnal Nasional Teknologi Komputer, 2025)
This research analyzes harmonic characteristics and their impact on energy efficiency in inverter air conditioner operation, as well as evaluates the effectiveness of harmonic mitigation methods. Using a MATLAB/Simulink-based simulation approach, the inverter AC system was modeled under various load levels and operating conditions. Results show that Total Harmonic Distortion (THD) of current is inversely proportional to load level, with the highest THD (30.3%) occurring at 25% load and the lowest (4.5%) at 100% load. Dominant harmonics were identified at orders 3, 5, and 7, contributing significantly to power losses. At low loads, harmonic distortion causes efficiency reduction of up to 10% and decreases the Coefficient of Performance (COP) by approximately 12%. Implementation of passive filters consisting of single-tuned filters for 5th order (250 Hz), 7th order (350 Hz) harmonics, and a high-pass filter for higher-order harmonics (>550 Hz) effectively reduces current THD by 70-80% and harmonic losses by up to 90%, significantly improving system efficiency and COP. The greatest efficiency improvement occurs at low loads, with COP increasing from 9.2 to 10.2 at 25% load. This research provides a foundation for developing power quality standards and more effective harmonic mitigation strategies to enhance energy efficiency in inverter AC systems.